2013
DOI: 10.5005/jp-journals-10019-1117
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dentulism, Partial Edentulism and Complete Edentulism in Rural and Urban Population of Malwa Region of India: A Population-based Study

Abstract: Background:The objective of this study was to evaluate the prevalence of dentulism, partial edentulism and complete edentulism in rural and urban population of Malwa region of India, who visited at department of prosthodontics for the first time. Materials and methods:An institution-based, cross-sectional study using the random sampling method was used to select the study sample of 1000 males and females. Data were collected using questionnaires and oral examination. Data were statistically analyzed using Chi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The psychological states and moods of patients significantly affect both the treatment processes and patient satisfaction with the treatment results. [13][14][15] According to Berggren and Meynert, if an individual has a predisposition to anxiety, a vicious circle of fear, anxietyinduced avoidance of dental care, deterioration of dentition, and feelings of guilt, shame and inferiority can occur. 16 In anxiety disorders, the main cause of physical symptoms is thought to be the sympathetic nervous system stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…The psychological states and moods of patients significantly affect both the treatment processes and patient satisfaction with the treatment results. [13][14][15] According to Berggren and Meynert, if an individual has a predisposition to anxiety, a vicious circle of fear, anxietyinduced avoidance of dental care, deterioration of dentition, and feelings of guilt, shame and inferiority can occur. 16 In anxiety disorders, the main cause of physical symptoms is thought to be the sympathetic nervous system stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Northern India revealed that between the ages of 43 and 53, 41.9% of females from rural areas and 48.2% urban females were partial edentulous while 58% of rural males and 51.7% urban males respectively were partially edentulous. 2 Acknowledging the financial constraints that individuals face, the acrylic partial dentures have been an economical and viable alternative to cast partial dentures in other countries too 3,4 .…”
mentioning
confidence: 99%